Unethical Postgraduate Supervision - Yahaghi, Hossein; Sorooshian, Shahryar; Yahaghi, Javad (Springer Netherlands, 2017)
Many years ago unprofessional supervisors were identified as one of the main reasons for the withdrawal of a student’s study. Recently in some universities, unethical supervision has become an increasing concern of students and ethic committees.